ANTIBACTERIAL EFFECTIVENESS OF RAMANIA LEAVES EXTRACT GEL (BOUEA MACROPHYLLA GRIFFITH) AGAINST THE GROWTH PSEUDOMONAS AERUGINOSA - Naura Firda Lunetta; Isyana Erlita; Dewi Puspitasari; I Wayan Arya Krisnawan Firdaus; Debby Saputera (FKG ULM, 2025)
Background: Pseudomonas aeruginosa is a gram-negative anaerobic bacteria and frequently associated with necrotic pulp infections. Necrotic pulp can be treated with root canal treatment (RCT). Sterilization of the root canal is one of the stages in RCT. The most used intracanal medicament in the sterilization stage of root canals is calcium hydroxide. This material may cause pulp irritation and inflammation in the surrounding tissues. These drawbacks are the reason for the necessity of alternative intracanal medicaments from natural materials such as ramania leaves (Bouea macrophylla Griffith). Flavonoids, saponins, tannins, steroids, and phenols are secondary metabolites derived from Ramania leaves that have been shown to have antibacterial properties. Purpose: To analyze the antibacterial effectiveness of ramania leaves extract gel (Bouea macrophylla Griffith) against Pseudomonas aeruginosa. Methods: Experimental study with a post-test only with control group design consisting of 5 treatment groups, namely ramania leaves extract gel with a concentration of 6,25%, 12,5%, 25%, 50%, and control (calcium hydroxide mixed with gel base) were repeated 5 times. The method used in the antibacterial test is using the agar well diffusion assay. Results: The Post-Hoc Bonferroni test confirmed statistically that there is significant differences among the treatment groups. Conclusion: The ramania leaves extract gel (Bouea macrophylla Griffith) at concentrations of 6.25%, 12.5%, 25%, and 50% has antibacterial potential against the growth of Pseudomonas aeruginosa. Keywords: antibacterial, bouea macrophylla griffith, intracanal medicament, necrotic pulp, pseudomonas aeruginosa, root canal treatment.